1978
DOI: 10.1007/bf02669922
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the solid fat content of commercial fats by pulsed nuclear magnetic resonance

Abstract: Fats ABSTRACTA method and instrumentation for measuring the solid fat content is reported that is both accurate and precise. It involves using transient nuclear magnetic resonance (NMR) measurements for determining the percentage of solids in commercial shortenings and hydrogenated oils at selected temperatures. The incorporation of a tempering step at 26.7 C for all samples before measurement has improved the precision of the solids content actually measured (+-0.2% solids) which approximates that of dilatome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…They are largely a function of the solid glyceride contents of the fats at those temperatures (13). Solid fat content (SFC) is therefore analyzed to indicate the crystallization tendency and finished product quality (14).…”
mentioning
confidence: 99%
“…They are largely a function of the solid glyceride contents of the fats at those temperatures (13). Solid fat content (SFC) is therefore analyzed to indicate the crystallization tendency and finished product quality (14).…”
mentioning
confidence: 99%
“…Methods of wide-line and pulsed NMR have been described by Haighton et af. (1971), Madison and Hill (1978) and van Boekel(l981). Mills and van der Voort (1981) compared direct and indirect wide-line NMR.…”
Section: Factors That Influence the Rheologieal Properties Of The Fatmentioning
confidence: 99%
“…(1 97 l), Madison and Hill (1978), Waddington (1980), van Boekel Most of the early investigations into the influence of solid fat content on the macroscopic rheological properties of plastic fats have been done on the effect of solid fût content on the penetration hardness (Bailey, 1950; de Man, 1962. It was found that the yield value (the definition and implications of this parameter will be discussed in Chapter 3, however, it can be viewed loosely as a measure of rnacroscopic hardness) was inversely proportional to the second power of the solid fat content.…”
Section: Solid Fat Contentmentioning
confidence: 99%